Meaning of mineral waters of Kapal depression for the development health tourism (Journal of Geography and Environmental Management, 2016)
The article presents data on results of a study of physical and chemical composition and the value of mineral waters of Kapal depression for development health tourism and recreation. Until recently thescientific research and design work are not received enough data balneological properties and brine of waters Kapal depression.
Keywords: mineral water; wellness; trace mineral; recreation